THE WORK HARD ETHIC OF TEACHER (ETOS KERJA KERAS GURU) DALAM PEMBELAJARAN SEBAGAI PILAR PENDIDIKAN YANG BERKARAKTE - sutarman, Sutarman (AL-MISBAH (Jurnal Islamic Studies), 2013)
Teacher isn?t one of all source of science in learning process. So, if the teacher needs survive in his or her contribution in the learning teaching process, they must do some innovations. Its means, the teacher  must have work hard ethic in doing to do the innovation, learning approach, chosing the metode and media. In order to make the learning teaching process run well, therefore the teacher is not only has mastered his or her competence but also has mastered the emotion quotion, spiritual quotion and has mastered the information, communication and technology. Beside that, the teacher who has work hard ethic,  is the teacher who has optimism. It means, in doing his task of the learning teaching process must have the strong motivation. So, the teacher will get the best achievement.